Spatial scaling of functional gene diversity across various microbial taxa - Zhou, Jizhong (National Academy of Sciences, 2008)
Understanding the spatial patterns of organisms and the underlying mechanisms shaping biotic communities is a central goal in community ecology. One of the most well documented spatial patterns in plant and animal communities is the positive-power law relationship between species (or taxa) richness and area. Such taxa–area relationships (TARs) are one of the principal generalizations in ecology, and are fundamental to our understanding of the distribution of global biodiversity. However, TARs remain elusive in microbial communities, especially in soil habitats, because of inadequate sampling methodologies. Here, we describe TARs as gene–area relationships (GARs), at a whole-community level, across various microbial functional and phylogenetic groups in a forest soil, using a comprehensive functional gene array with >24,000 probes. Our analysis indicated that the forest soil microbial community exhibited a relatively flat gene–area relationship (slope z = 0.0624), but the z values varied considerably across different functional and phylogenetic groups (z = 0.0475–0.0959). However, the z values are several times lower than those commonly observed in plants and animals. These results suggest that the turnover in space of microorganisms may be, in general, lower than that of plants and animals.